Results of the assessment of the level of literacy of the Ukrainian population in matters of health and use of medicines - Elizaveta Kovtun; Alina Volkova (Pensoft Publishers, 2023)
An instrument for assessing the health literacy of the population in matters of health and use of medicines was developed and a survey was conducted among different age groups of the Ukrainian population. Based on the analysis of the data obtained, it is proved that health literacy and pharmaceutical literacy in particular are an important factor in shaping health outcomes and quality patient interaction with doctors and pharmacists. The data obtained at this stage emphasize the need to improve the level of health and pharmaceutical literacy of the population, taking into account the needs, basic knowledge and skills of each age group. The study also demonstrates the relevance of regular assessment of the population's awareness of health issues and the use of medicines in order to understand how each component of health literacy may differ between the identified age subgroups (e.g., adolescents, the elderly), with further development of adapted approaches to forming an appropriate level of knowledge on health issues and rational use of medicines and the specifics of their use for different segments of the population.